Invariant NKT cells reduce the immunosuppressive activity of influenza A virus-induced myeloid-derived suppressor cells in mice and humans. - De Santo, C; Salio, M; Masri, S; Lee, L; Dong, T; Speak, A; Porubsky, S; Booth, S; Veerapen, N; Besra, G; Gröne, H; Platt, F; et al. (2008)
Infection with influenza A virus (IAV) presents a substantial threat to public health worldwide, with young, elderly, and immunodeficient individuals being particularly susceptible. Inflammatory responses play an important role in the fatal outcome of IAV infection, but the mechanism remains unclear. We demonstrate here that the absence of invariant NKT (iNKT) cells in mice during IAV infection resulted in the expansion of myeloid-derived suppressor cells (MDSCs), which suppressed IAV-specific immune responses through the expression of both arginase and NOS, resulting in high IAV titer and increased mortality. Adoptive transfer of iNKT cells abolished the suppressive activity of MDSCs, restored IAV-specific immune responses, reduced IAV titer, and increased survival rate. The crosstalk between iNKT and MDSCs was CD1d- and CD40-dependent. Furthermore, IAV infection and exposure to TLR agonists relieved the suppressive activity of MDSCs. Finally, we extended these results to humans by demonstrating the presence of myeloid cells with suppressive activity in the PBLs of individuals infected with IAV and showed that their suppressive activity is substantially reduced by iNKT cell activation. These findings identify what we believe to be a novel immunomodulatory role of iNKT cells, which we suggest could be harnessed to abolish the immunosuppressive activity of MDSCs during IAV infection.